Combating "dread shed": The impact of overlapping topical and oral minoxidil on temporary hair shedding during oral minoxidil initiationCapsule Summary - Ambika Nohria, BA; Deesha Desai, BS; Michelle Sikora, BS; Soutrik Mandal, PhD; Jerry Shapiro, MD; Kristen Lo Sicco, MD (Elsevier, 2024)
Background: Low dose oral minoxidil (LDOM) is a preferred treatment for alopecia due to ease of use and efficacy. While LDOM is typically well tolerated, patients may experience a temporary increase in hair shedding starting treatment, colloquially regarded as "dread shed". One proposed method to combat this is to overlap therapies by maintaining use of topical minoxidil when initiating LDOM. Objective: To evaluate the impact of maintaining topical minoxidil when initiating LDOM on "dread shed". Methods: We performed a retrospective chart review of patients seen at New York University Langone Health Dermatology from January 1, 2008 to August 1, 2023 prescribed LDOM. Results: A total of 115 patients met inclusion criteria, of whom 37 maintained use of topical minoxidil when initiating LDOM. Six patients experienced "dread shed" when initiating LDOM, 2 of whom overlapped therapies. We did not find that overlapping therapies had a significant impact on decreasing rates of "dread shed". Limitations: Limitations include retrospective design, sample size, and subjective patient-reported assessment of hair shedding. Conclusions: A total of 5.2% of patients experienced dread shed, which is lower than previously reported in literature. Maintaining topical minoxidil during LDOM initiation does not significantly impact "dread shed". This remains a significant side effect deserving of further research.